4C.001 Conceptualising 'injury' in Nepal: Building shared understandings as a foundation for engagement. (14th March 2021) - Paudel, Sunil; Subedi, Madhusudan; Brangan, Emer; Mytton, Julie; Joshi, Sunil
Abstract : Background: When designing a logo for the Nepal Injury Research Centre a predicament arose: there is no direct Nepali translation for the word 'injury'. A 'loan-word' was used, but this highlighted a broader issue – what do different stakeholders in Nepal understand when we talk about injuries, and what implications might this have for engaging them in research/intervention? Methods: To ground our exploration of this topic meaningfully for different stakeholders, we iteratively refined our research design. Experts in injury prevention/occupational health/sociology prepared a proposal, shared through consultation in academic circles. Feedback informed design of an engagement-workshop in December 2019, involving 36 participants from anthropology/sociology/social-work/development-work and health backgrounds. Outputs informed design of the next stage, which is ongoing. Results: Professional backgrounds influenced concepts of injury that emerged; where sociologists highlighted the role of social structures, health professionals referenced disruption of 'health' as defined by WHO. In addition to physical harms, participants mentioned economic, social/cultural, mental/psychological and spiritual harms. Groups defined injury-types differently, and categorized/grouped these in diverse ways–not all perspectives aligned with WHO International Classification of diseases. Conclusion: Multi-dimensional concepts of injury have implications for how we engage with policy-makers on prevention, and design of interventions to mitigate harm. Varied concepts of injury could inform epidemiological survey design, to elicit injuries which might not otherwise be reported. Learning Outcomes: Exploring our research field from first principles can help surface our underlying assumptions, as well as sensitizing researchers to the need to identify/engage with meanings important to stakeholders we seek to influence.